Baru meal on the performance of dairy calves: an alternative to reduce costs in the breeding phase (Acta Scientiarum. Animal Sciences, 2025)
The objective of this study was to evaluate the intake, performance, and economic viability of crossbred Holstein calves (n = 16) fed diets containg different levels of baru meal (Dipteryx alata . Vog) as a replacement for corn (0, 25, 50, and 72%). Total solid feed, concentrate, and forage intake, nutrient intake, weight gain, ingestive behavior, and economic viability were evaluated. Total solid feed and concentrate intake linearly increased (p0.05). Baru meal inclusion linearly increased the intake of crude protein, minerals, ether extract, and non-fibrous carbohydrates. Concentrate feeding time exhibited a quadratic effect, with a maximum of 75.92 min. day-1 at 67% replacement. Economic analysis showed that the 50% replacement diet result in higher feed costs but lower cost per kilogram of gain. The inclusion of baru meal up to 72% of corn replacement increased intake without compromising the performance during preweaning phase. A 50% replacement provided the best economic return.